Trends in incidence and survival in patients with gastrointestinal neuroendocrine tumors: A SEER database analysis, 1977-2016 - Liu, Miao; Wei, Lingge; Liu, Wei; Chen, Shupeng; Guan, Meichao; Zhang, Yingjie; Guo, Ziyu; Liu, Ruiqi; Xie, Peng (Frontiers in Oncology, 2023)
Objectives: We aimed to determine trends in incidence and survival in patients with gastrointestinal neuroendocrine tumors (GI-NETs) from 1977 to 2016, and then analyze the potential risk factors including sex, age, race, grade, Socioeconomic status (SES), site, and stage. Methods: Data were obtained from Surveillance, Epidemiology, and End Results Program (SEER) database. Kaplan-Meier survival analysis, relative survival rates (RSRs), and Cox proportional risk regression model were used to evaluate the relationship between these factors and prognosis. Results: Compared with other sites, the small intestine and rectum have the highest incidence, and the appendix and rectum had the highest survival rate. The incidence is higher in females than in males, and the same trend exists for survival. Blacks had a higher incidence rate than whites, but similar survival rates. incidence and survival rates were lower for G3&4 than for G1 and G2. Age, stage, and grade are risk factors. Conclusions: This study described changes in the incidence and survival rates of GI-NETs from 1977 to 2016 and performed risk factor analyses related to GI-NETs.